"挤压组织化对大豆蛋白结构及大豆组织 蛋白品质影响的研究进展""Effect of extrusion texturization on the structure of soybean protein and the quality of textured soybean protein products: A review" - 马润豪1，安红周1,2，薛义博2，黄亚男3，杜艳1,2MA Runhao1，AN Hongzhou1,2，XUE Yibo2，HUANG Yanan3，DU Yan1,2 (Zhongguo youzhi)
大豆组织蛋白是一种以大豆蛋白为原料，运用挤压机的高温、高压、高剪切力使蛋白质分子原有结构改变，并最终形成具有纤维结构、口感类似动物肉的产品。旨在为大豆组织蛋白产品的研发提供理论参考，通过介绍大豆蛋白挤压组织化过程，对挤压过程中大豆蛋白的结构变化进行综述，重点阐述了挤压组织化对大豆蛋白分子间相互作用与蛋白质构象的影响，总结了原辅料及挤压工艺参数对大豆组织蛋白产品品质的影响。在大豆蛋白的组织化过程中，蛋白质的空间结构、分子间作用力发生改变，以二硫键为主的共价键对于形成纤维状和网状的蛋白质结构发挥了重要作用，不同的原辅料与挤压工艺参数对于大豆蛋白的组织化度也有不同的影响。未来，需要加大对挤压设备的创新改进，提高原料种类的适应性，开发适宜的本土化大豆组织蛋白产品。 Textured soybean protein (TSP) is a type of product that uses soybean protein as raw material and uses the high temperature, high pressure, and high shear force of the extruder to change the initial structure of protein molecules, ultimately forming a product with a fibrous structure and a taste similar to animal meat. Aiming to provide a theoretical reference for the research and development of TSP products, by introducing the extrusion texturization process of soybean protein, the structural changes of soybean protein in the extrusion process were reviewed, focusing on the effects of extrusion texturization on the intermolecular interactions and protein conformation of soybean protein, and the effects of raw and auxiliary materials and extrusion process parameters on the quality of TSP were summarized. During the texturization process of soybean protein, the spatial structure and intermolecular forces of protein changed, and the covalent bonds, mainly disulfide bonds, played an important role in the formation of the fibrous and reticular protein structure. Different raw and auxiliary materials and extrusion process parameters had different influences on the degree of texturization of soybean protein. In the future, it is necessary to increase innovation and improvement of extrusion equipment, improve the adaptability of raw material types, and develop TSP products suitable for localization.